Significance of Akhmet Baitursynuly’s contribution to the development of Kazakh journalism and publicism - Yertassova, Г.Қ.; Sak, Қ.Ө. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2022)
Abstract. In the early twentieth century, the convergence of Kazakh intellectual forces around the national press was born of social necessity. It was the injustice and unbearable political and social situation that led them to unite and act together. Akhmet Baitursynuly is a unique and wise person who has made an invaluable contribution to the prosperity and development of national thought in such a difficult time. During this period, Akhmet Baitursynuly, who began to realize his own civic position, was faced with a thorny path of selfless service to the Alash movement. At a time when the throne of the White Tsar really shook, and the era of tsarist government was coming to its logical end, Akhmet had to stop teaching for a time and chose journalism. Thus, through the Kazakh Press, he aroused the spirit of the country and began to take care of the permanent separation from colonial oppression. At first, it was easy to make a choice, but for his political views, he quickly fell on the side of gendarmes. But Akhmet Baitursynuly did not lose his heart in the name of the nation. It was obvious that he would not forgive himself if he backed down. The Alash figure set himself the task of revealing Kazakh literature, providing information and educational materials through the press, and analyzing the burning problems within the country to the fullest. In his artistic and journalistic articles published in newspapers and magazines in the Kazakh language, published at the beginning of the XX century, Akhmet exposed the tyranny and cruelty of the Tsarist colonial system, the chauvinist policy of the great power in matters of land, Human Rights, country, urged the people to free themselves from the darkness, strive for education, unite against colonial oppression.